THE ROLE OF DIETARY AND SUPPLEMENTATION INTERVENTIONS IN ALLEVIATING ADHD SYMPTOMS - Balon, Sandra; Maćkowski, Michał; Białowąs, Weronika; Białowąs, Monika; Urban, Kacper Piotr; Śmietana, Adam; Sojka, Natalia Julia; Dubiel, Karolina Maria; Magnowski , Jakub Jan; Szwed, Piotr (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Attention-Deficit/Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder affecting both children and adults. Standard pharmacological treatment, while effective, carries the risk of adverse effects, prompting patients to seek complementary therapies. Modifiable factors, such as diet and supplementation, are increasingly recognized as significant elements regulating central nervous system functioning.Objective: The aim of this review is to synthesize and critically analyze current scientific evidence regarding the impact of dietary interventions (elimination diets, dietary patterns) and supplementation (fatty acids, micronutrients, vitamins) on the severity of ADHD symptoms.Methodology: A review of available scientific literature was conducted using PubMed, Scopus, and Google Scholar databases. The analysis included meta-analyses, systematic reviews, and randomized controlled trials (RCTs) published over the last 20 years, focusing on publications with high methodological rigor.Results: The review indicates that the oligoantigenic diet demonstrates high efficacy in a specific subgroup of patients with food hypersensitivity, while the elimination of artificial food colors yields a small but significant effect in the general population. Unhealthy dietary patterns (Western diet) correlate with a higher risk of ADHD diagnosis. Regarding supplementation, the strongest evidence supports omega-3 fatty acids (with a predominance of EPA). Supplementation with iron, zinc, magnesium, and vitamin D is clinically effective primarily in cases of correcting confirmed deficiencies.Conclusions: Endogenous processes regulating ADHD symptoms are modulated by a complex interaction of nutritional factors. Although diet and supplementation do not replace pharmacotherapy in severe cases, they constitute a valuable adjunctive (additive) strategy. A holistic approach, incorporating personalized nutrition and safety monitoring, should be considered an element of standard care for patients with ADHD.